HUBUNGAN DISIPLIN DENGAN PRESTASI BELAJAR IPA SISWA DI KELAS VII SMP N 10 PEMATANGSIANTAR - Simajorang, Anna Tresya; Hulu, Irwan Lihardo; Sinaga, Dian Perayanti (Jurnal Metabio, 2024)
This study was conducted with the aim of determining the relationship between learning discipline and science learning achievement of class VII students of SMP Negeri 10 Pematangsiantar in the 2021/2022 Academic Year. This study was conducted from February to April 2022. The population in the study was 224 students and the number of samples was 35 students. The instruments used in this study were questionnaires and DKN. This study was proven by correlation tests, t tests and determination tests. The average score of science learning achievement of class VII students of SMP Negeri 10 Pematangsiantar in the 2021/2022 Academic Year was 79.97, which is a fairly high average learning achievement. The average score of the science learning discipline questionnaire of class VII students of SMP Negeri 10 Pematangsiantar in the 2021/2022 Academic Year was 73.28, which is a fairly high average questionnaire. From the results of the correlation test, the correlation between discipline and science learning achievement of class VII students of SMP Negeri 10 Pematangsiantar in the 2021/2022 Academic Year was obtained r = 0.82. Based on the qualification of the correlation coefficient, the correlation of the two variables above is included in the correlation coefficient which is quite high. From the results of the hypothesis testing with the t-test, the calculated t = 8.27 was obtained and at the significance level ∝ = 0.05 and dk = 33, the t-table = 2.034 was obtained. So the calculated t is greater than the t-table, so in this case Ho is rejected and Ha is accepted, meaning that there is a significant relationship between learning discipline and science learning achievement of class VII students of SMP Negeri 10 Pematangsiantar in the 2020/2021 Academic Year. Based on the results of the determination test, the contribution/relationship between discipline and science learning achievement of class VII students of SMP Negeri 10 Pematangsiantar in the 2021/2022 Academic Year was 67.24%. This means that the science learning achievement achieved by class VII students of SMP Negeri 10 Pematangsiantar, 67.24% is influenced by discipline in learning. It is concluded that there is a significant relationship between learning discipline and science learning achievement of class VII students of SMP Negeri 10 Pematangsiantar in the 2021/2022 Academic Year.